Social Behavior in Citizen Coexistence, Individual and Collective Responsibility - Montoya Párraga, Lucy Alcira; García Sarria, Juan José; Gonzalez Cortes, Armando (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research arises from addressing social behaviors and their influence on citizen coexistence. For this, an understanding was made from the following perspectives: culture, norm, family, school and pedagogy, transversalized by Law 1801 of 2016, Code of Coexistence and Citizen Security. The objective is to analyze from nuclei such as the family, the school and the norm, the process of social behavior and its impact on citizen coexistence, from individual and collective responsibility, the documentary qualitative study methodology was obtained. Obtaining little encouraging results due to the increase in behaviors contrary to the coexistence of Colombian society.